1996
DOI: 10.1002/(sici)1097-0142(19960115)77:2<237::aid-cncr3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Biologic characteristics of esophageal epithelial dysplasia assessed by proliferating cell nuclear antigen

Abstract: PCNA expression may be a useful marker to reflect the biologic characteristics of esophageal dysplasia, suggesting that a high grade of dysplasia is as serious a lesion as esophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For example, a long‐term follow‐up study of patients with oesophageal dysplasia showed that 30% of the cases progressed to squamous cell carcinoma over a follow‐up period of 2.5– 6.5 years 3 . Possible molecular bases of this process have been examined and several abnormalities have been described in dysplasia, including genetic instability, DNA aneuploidy, loss of heterozygosity, mutation of the tumour suppressor gene p53 , and a high proliferating cell nuclear antigen (PCNA) index 4–10 . However, much remains to be clarified about the dysplasia–carcinoma sequence of the oesophagus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a long‐term follow‐up study of patients with oesophageal dysplasia showed that 30% of the cases progressed to squamous cell carcinoma over a follow‐up period of 2.5– 6.5 years 3 . Possible molecular bases of this process have been examined and several abnormalities have been described in dysplasia, including genetic instability, DNA aneuploidy, loss of heterozygosity, mutation of the tumour suppressor gene p53 , and a high proliferating cell nuclear antigen (PCNA) index 4–10 . However, much remains to be clarified about the dysplasia–carcinoma sequence of the oesophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Autoradiographic studies utilizing tritiated thymidine reported an increase in the population of proliferative cells in some patients with Barrett's metaplasia. 14 In addition, immunohistochemical studies using antibodies against proliferation-associated antigens, such as proliferating cell nuclear antigen (PCNA) [15][16][17][18] and Ki-67, 19,20 reported a positive correlation between cell proliferation and increasing degrees of dysplasia in Barrett's epithelium. Other studies utilizing flow cytometric analysis to assess Ki-67 labeling, however, found no differences in Ki-67 expression among Barrett's without dysplasia, low grade dysplasia, high grade dysplasia, or adenocarcinoma.…”
mentioning
confidence: 99%
“…In this study, we estimated the cell proliferative activity and carcinogenesis of esophageal dysplastic lesions using PCNA analysis [10]. PCNA was first reported as one of the nuclear antigens reacting with an autoantibody in the sera of patients with systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…The PCNA LI is expressed as a percentage of the positive cells [10]. In normal epithelium, the PCNA LI was low (7.5% ± 4.1%) in the basal layer, and about 17.3% ± 7.3% in the parabasal layer (Table 3).…”
Section: Frequency Of Dysplasia In Esophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation